Uso de óleo à base de linhaça na dieta e perfis de ácidos graxos do plasma e do líquido folicular em éguas Mangalarga Marchador - Viafara, Jesus Alfonso Sánchez (2015)
The objective was to detect the presence of polyunsaturated fatty acids (PUFA) in the blood circulation and in the ovarian follicular fluid as a result of linseed oil supplementation in the diet. Six Mangalarga Marchador mares between 2.5 and 22 years old, weighing 397±31.89 kg, with body score of 3 and 6.5, kept on native pasture were used. In a switch over design, mares were randomly allocated to receive 150 ml of vegetable oil daily, containing PUFA n3(62.23 g ALA, 20.34 g LA, 2.27 g EPA, 2.32 g DHA), (n=3) or no supplementation (n=3) in a first replicate. Blood and follicular fluid samples were taken on the first (D0) and every 10 days until the end of the supplementation period (D10-D30). After a 14 day interval, mares were switched across the treatments for a second replicate. Lipid profiles were determined by gas chromatography. Data were submitted to the MIXED and REG procedures of SAS®. In the plasma the concentrations of linolenic LNA acid in total fatty acids were higher (P=0.006) in the supplemented compared to the control group (1.89±0.13 VS. 1.49±0.13%). In the follicular fluid the concentrations of linoleic acid were similar between treatments (10.9±2.23 VS. 7.61±2.22 %, for supplemented and controls, respectively) and across periods (5.75±3.33, 12.87±4.09 and 14.2±4.09% for periods 1 (before treatments started), 2 and 3 (10 and 20 days after treatments started, respectively) for the supplemented group, and 7.55±3.34, 9.01±4.08 and 6.27±4.08%, for controls, respectively). However the concentrations of DHA tended to be higher (P=0.06) in the control group. There were positive correlations between plasma linoleic acid and follicular fluid araquidonic acid (P=0.0106; r2=0. 13) and between plasma linolenic acid and follicular fluid EPA (P=0.0004; r2=0.2544). In conclusion, data indicated a low to moderate relationship between dietary linseed-based oil supplementation studied and circulating and follicular fluid PUFA contents in mares.